2021
DOI: 10.1021/acs.estlett.1c00337
|View full text |Cite
|
Sign up to set email alerts
|

Development of Electrospun Nanofibrous Filters for Controlling Coronavirus Aerosols

Abstract: Airborne transmission of SARS-CoV-2 plays a critical role in spreading COVID-19. To protect public health, we designed and fabricated electrospun nanofibrous air filters that hold promise for applications in personal protective equipment (PPE) and the indoor environment. Due to ultrafine nanofibers (∼300 nm), the electrospun air filters had a much smaller pore size in comparison to the surgical mask and cloth masks (a couple of micrometers versus tens to hundreds of micrometers). A coronavirus strain served as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 40 publications
(72 reference statements)
3
52
0
Order By: Relevance
“…From a literature review of numerous cloth masks, Clase et al [ 25 ] reported that cloth layering improves filter performance, but they did not discuss the relationship between this improvement and pressure drop. Shen et al [ 26 ] also reported the usefulness of nanofiber filters in comparison with nonwoven fabrics. However, they did not discuss pressure drop.…”
Section: Discussionmentioning
confidence: 99%
“…From a literature review of numerous cloth masks, Clase et al [ 25 ] reported that cloth layering improves filter performance, but they did not discuss the relationship between this improvement and pressure drop. Shen et al [ 26 ] also reported the usefulness of nanofiber filters in comparison with nonwoven fabrics. However, they did not discuss pressure drop.…”
Section: Discussionmentioning
confidence: 99%
“…So, recently, the outbreak of the virus has made everyone think about air quality and the provision of proper air filtration systems. Besides, to protect general health, air filters based on electrospun nano-fibers that have antimicrobial properties have been expanded and can be used to provide proper ventilation systems and masks [ [18] , [19] , [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Particularly, our previous study has underscored that electrospun membranes caught up to 99.9% of coronavirus aerosols. 15 …”
Section: Introductionmentioning
confidence: 99%
“…We are one of the first to use coronavirus aerosols to challenge air filters and evaluate filtration performance, also as suggested by our previous study. 15 Compared to other surrogates, murine hepatitis virus A59 (MHV-A59) best simulates the environmental and biological behavior of SARS-CoV-2 in filtration and disinfection because both viruses are β-coronaviruses and they have a similar virion size. 26 Moreover, we elucidate the molecular-level mechanism of how photooxidation damaged coronaviruses, impaired the biological functions of the viruses, and eventually inactivated the viruses for the first time.…”
Section: Introductionmentioning
confidence: 99%